Phenological Growth Stages of Chinese Quince (Psyudocydonia sinensis C.K. Schneid.): Codification and Description According to the BBCH Scale - Grygorieva, Olga; Klymenko, Svitlana; Horčinová Sedláčková, Vladimíra; Šimková, Jana; Brindza, Ján (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The aim of the study was the determination of the main phenological growth stages less known species of Chinese quince in the conditions of Slovakia. For the study of the issue we used 6 individuals produced in the Arboretum Mlyňany (Slovak Republic). The age of them will be estimated approximately 30 years. Experimental data gained in years 2016–2017 in phenological studies of Chinese quince (Pseudocydonia sinensis C.K. Schneid.) were utilized to describe phenological growth stages of given species. For the description of phenological growth stages, it was used BBCH Monograph (1997). Phenological observations and time data collection were provided at regular intervals in the text form and photodocumentation. Complex phenological growth stages were processed based on the phenological records. Resulting data will be used for the list of descriptors preparation specified for the given species and oriented on the practical utilization in the research, breeding and genetic resources investigation. A feature of the system is that homologous stages of different crops are presented by the same codes.